Odniesienia intertekstualne obecne w tłumaczeniu dramatu Ślub Witolda Gombrowicza na język kaszubski w świetle badań komparatystycznych - Makurat, Hanna (Przekłady Literatur Słowiańskich, 2014)
Intertextual references present in the translation of Witold Gombrowicz’s drama The Marriage into Kashubian in the light of comparative researches This article is devoted to the issue of intertextuality in the translation of Witold Gombrowicz’s drama The Marriage into the Kashubian language considered on the ground of comparative researches. The analysis includes intertextual relationships founded on the basic relationship between the original and the translation, consisting of intensification or weakening of familiarity and strangeness elements. In particular it consists of intertextuality at the level of polysemy, intertextuality at the level of metaphor and intertextuality at the level of indicators of text organisation. The latter category includes problems with the reflection of the local dialect style, spelling and rhymes experiments which were all present in the original of the drama. It was not always possible to reflect the language experiments conducted by Witold Gombrowicz in the translation into the Kashubian language, even though it was a translation into a closely related language. Key words: intertextuality, Kashubian, Witold Gombrowicz, West Slavic languages, translation